Engineering pest tolerance through plant-mediated RNA interference. (April 2021) - Chung, Seung Ho; Feng, Honglin; Jander, Georg
Abstract : Expression of insect-targeted RNA interference (RNAi) constructs in transgenic plants is a promising approach for agricultural pest control. Compared to conventional chemical insecticides, RNAi target specificity is high and the potential for negative environmental effects is low. However, although numerous laboratory studies show insect growth inhibition by double stranded RNA or artificial microRNA, few of these constructs have been moved into commercial application as genetically engineered plants. Variation in RNA degradation, uptake, processing, and systemic transport in insects can influence interspecific and intraspecific differences in RNAi efficacy and the development of resistance to RNAi in agricultural settings. Further research is needed, both to identify optimal gene targets for efficient RNAi in pest species and to reduce the potential for off-target effects in beneficial species.